The determinants of competitiveness in global palm oil trade - Hansen Tandra; Arif Imam Suroso; Yusman Syaukat; Mukhamad Najib (Economies, 2022)
Palm oil is an essential commodity used in the manufacture of various daily products and is highly competitive with vegetable oil. However, the palm oil competition is fierce and complex due to movement of palm oil trade. The study examined the determinant, stability, and duration of competitiveness in the global palm oil trade involving countries worldwide. This research was analyzed from 1996 to 2019 using descriptive analysis, panel regression, stability, and Kaplan-Meier tests. The results showed that palm oil supply in the global market is centralized with distributed demand. The competitiveness of palm oil based on revealed symmetric comparative advantage (RSCA) and trade balance index (TBI) is similar to its suppliers globally. The positive factors that determine the competitiveness in the global palm oil trade are population and import of animal or vegetable fats and oils. GDP per capita and dummy RSPO negatively affect competitiveness. The stability and duration analysis showed that the global palm oil market is highly competitive.
Keywords: 330; comparative advantage; competitiveness; global market; palm oil; trade